Pengaruh Stres Kronik terhadap Otak: Kajian Biomolekuler Hormon Glukokortikoid dan Regulasi Brain-Derived Neurotrophic Factor (BDNF) Pascastres di Cerebellum - Desby Juananda; Dwi Cahyani Ratna Sari; Djoko Prakosa2,; Nur Arfian; Mansyur Romi (Jurnal Ilmu Kedokteran, 2015)
The brain is the central organ of stress adaptation, and is also a target of stress. Chronic stress may result in abnormalchanges in brain plasticity; include dendritic retraction, neuronal toxicity, and suppression of neurogenesis andaxospinous synaptic plasticity. Repetitive stress exposure will gradually change the electrical characteristic, morphologyand proliferative capacity of neurons. Among brain region, the cerebellum is known to be severely affected by oxidativedamage associated with glucocorticoids level. It is believed due to the highest levels of glucocorticoid receptorslocalized in the external granular layer. BDNF, a member of neurotrophin family, is known to be a strong survivalpromoting factor, and plays a critical role in cell proliferation and differentiation, neuronal protection, and the regulationof synaptic function in the central nervous system. BDNF is highly expressed in the cerebellum, mainly in granulecells. Both acute and chronic stress change BDNF expression in the brain. Although the impact of stress on BDNFlevels showed the different results, BDNF is believed to protect neurons from injuries caused by stress.